2021
DOI: 10.3390/life11090989
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Plasma Protein N-Glycan Peaks Are Potential Predictors of Semen Pathology and Sperm Chromatin Maturity in Men

Abstract: Background: Male infertility is increasingly becoming a health and demographic problem. While it may originate from congenital or acquired diseases, it can also result from environmental exposure. Hence, the complexity of involved molecular mechanisms often requires a multiparametric approach. This study aimed to associate semen parameters with sperm DNA fragmentation, chromatin maturity and seminal plasma protein N-glycosylation. Methods: The study was conducted with 166 participants, 20–55 y old, 82 normozoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Terminal Lewis x /Lewis y N- glycans in seminal plasma were implicated in the suppression of innate and adaptive immune responses . Due to the variety potential roles in semen function during fertilization, seminal plasma glycoproteins raise widespread concerns in applications as clinical biomarkers. Therefore, a comprehensive and global exploration of glycosylation in seminal plasma will expand our understanding of reproductive biology in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Terminal Lewis x /Lewis y N- glycans in seminal plasma were implicated in the suppression of innate and adaptive immune responses . Due to the variety potential roles in semen function during fertilization, seminal plasma glycoproteins raise widespread concerns in applications as clinical biomarkers. Therefore, a comprehensive and global exploration of glycosylation in seminal plasma will expand our understanding of reproductive biology in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Concanavalin A is able to bind biantennary complex glycans, while does not recognize those with three or four antennae. Marić et al [ 142 ] in their SP N-glycome analysis identified a decreased level of biantennary bisialylated glycans (with or without fucose) accompanying increasing sperm chromatin maturity. This may be read as relatively increased glycan branching accompanying the impaired semen pattern.…”
Section: Seminal Plasma Glycomementioning
confidence: 99%
“…These cells, presenting a panel of immunomodulatory lectins as described in the former paragraphs, enter the microenvironment created by seminal plasma, which makes the direct interaction possible. The second fact that should be emphasized is the presentation of glycoepitopes, which can potentially be ligands for lectins in SP glycoproteins, and also the reports on the changes in their glycosylation pattern, observed in the patients with fertility disorders [ 142 , 144 ], classified as: oligozoospermia—sperm count < 16 mln/mL; asthenozoospermia—<32% of sperm with progress motion; teratozoospermia—<4% sperm with correct morphology; and normozoospermia—the semen fulfilled the WHO recommended values, while male infertility factor was suspected. So far, data on the direct interaction of seminal plasma glycoconjugates with endogenous lectins of the immune system are limited.…”
Section: Seminal Plasma Glycomementioning
confidence: 99%
“….jrasb.com motility; improvement of sperm fertilisation characters; reduction of any alteration that can occur in the endocrine and replacement of testicular damages; and reduction of germ cell apoptosis by improving testicular histology [80,81,82]. …”
mentioning
confidence: 99%